Antioxidant and Hypolipidemic Activity of the Hydroethanolic Extract of Curatella americana L. Leaves - Lopes, Rafael Henrique Oliveira (Oxid Med Cell Longev, 2016)
High levels of reactive oxygen species in the body and hyperlipidemia are key factors for the development of cardiovascular diseases such as atherosclerosis. The present study investigated the antioxidant and hypolipidemic activity of hydroethanolic extract of Curatella americana L. leaves (ExC). The antioxidant activity of ExC was assessed by 2,2-diphenyl-1-picrylhydrazyl free radical (DPPH) scavenging capacity and protection against hemolysis induced by 2,2′-azobis(2-amidinopropane) dihydrochloride (AAPH), followed by quantification of malondialdehyde (MDA). Wistar rats with hyperlipidemia induced by high-fructose diet (60%) were treated for 60 days with water, simvastatin (30 mg·Kg(−1)), ciprofibrate (2 mg·Kg(−1)), and ExC (200 mg·Kg(−1)). ExC revealed IC(50) of 6.0 ± 0.5 μg·mL(−1), an intermediary value among positive controls used in the assay of DPPH scavenging capacity. At all concentrations (50 to 125 μg·mL(−1)) and times (60 to 240 min) evaluated, ExC protected erythrocytes against AAPH-induced hemolysis, which was confirmed by lower MDA levels. In vivo tests showed a reduction of 34 and 45%, respectively, in serum concentration of cholesterol and triglycerides in hyperlipidemic rats treated with ExC, a similar effect compared to the reference drugs, simvastatin and ciprofibrate, respectively. Together, the results showed the antioxidant activity of ExC and its ability to improve the serum lipid profile in hyperlipidemic rats.